2006
DOI: 10.1158/1078-0432.ccr-05-0245
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography: Real-time Imaging of Bronchial Airways Microstructure and Detection of Inflammatory/Neoplastic Morphologic Changes

Abstract: Purpose: Current diagnostic imaging modalities for human bronchial airways do not possess sufficient resolution and tissue penetration depth to detect early morphologic changes and to differentiate in real-time neoplastic pathology from nonspecific aberrations. Optical coherence tomography (OCT) possesses the requisite high spatial resolution for reproducible delineation of endobronchial wall profiling. Experimental Design: To establish whether OCT could differentiate between the composite micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 27 publications
1
69
0
1
Order By: Relevance
“…Most important is the question of whether OCT can identify characteristics within the airway wall that predict BT responders. Inflammation is visible on OCT [7,15] and, notably, in this study, the BT responder showed thickened airway wall without evidence of inflammation in the epithelial layer at baseline compared to the nonresponder.…”
Section: To the Editormentioning
confidence: 49%
“…Most important is the question of whether OCT can identify characteristics within the airway wall that predict BT responders. Inflammation is visible on OCT [7,15] and, notably, in this study, the BT responder showed thickened airway wall without evidence of inflammation in the epithelial layer at baseline compared to the nonresponder.…”
Section: To the Editormentioning
confidence: 49%
“…OCT can be used to conduct large-volume in vivo microscopy of tissue with resolutions comparable to low-power microscopy (18). OCT has been used to accurately detect and diagnose pathology in vivo for a number of years (17)(18)(19)(20)(21)(22)(23)(24) and has been used to assess the fine microarchitectural features in both normal and pathologic lung (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 99%
“…In its conventional form, OCT allows subsurface airway analysis to a depth of 2-3 mm, providing an ''optical biopsy'' approaching histological resolution. Respiratory applications focus on the detection of malignant and dysplastic epithelial changes [10,11]. Anatomical OCT (aOCT) is a modification of conventional OCT designed to range over larger distances to permit real-time macroscopic imaging of hollow organs [12].…”
mentioning
confidence: 99%